Pandas - Anne Schreiber; National Geographic Kids
The whole world loves panda bears. Everyone loves to watch them play, climb, cuddle, and chew. But careful, they can scratch too$1 (Bjust look at that tree! Pandas live in wild places very far away, and they are the STAR ATTRACTIONS of every zoo that keeps them safe and well, all over the world.s